DESIGN OF FISHERMAN BOAT PULLING MACHINE FOR IMPROVING WORK EFFICIENCY AND WELFARE OF TRADITIONAL FISHERMEN AT PASIE KATAPIANG BEACH, PADANG PARIAMAN - Effiandi, Nota; Irwan, Irwan; Seno, Abdi; Arifian, Naf'an; Haris, Haris; Nusyirwan, Nusyirwan; Hamdani, Rifqi; Sumiati, Ruzita (International Journal of Multidisciplinary Research and Literature, 2024)
This study aims to design an efficient boat-pulling machine to support traditional fishermen at Pasie Katapiang Beach, Padang Pariaman. The research method employed is the design of the tool based on the principles of design engineering, involving a systematic process in creating a machine that can assist fishermen in the boat docking process more efficiently. Through calculations and planning, it was found that the force required to pull the fishermen's boat is 6,522.88 N, using a shaft made of ST 37 material with a diameter of 22.413 mm. The rotations generated on the transmission shaft are 2000 rpm, while on the wheel and drum shafts are 750 rpm and 500 rpm, respectively. The selection of a slip clutch with 2 bolts on the transmission shaft and the use of pillow block bearing ucp 206 ass 30 with specified bearing life estimates have been considered in the machine design. Practical test results indicate that the time required to reel or pull the boat is 0.98 minutes. In this research, the design of the boat-pulling machine meets operational needs. It has the potential to positively contribute to improving the work efficiency and welfare of traditional fishermen in the field